Going alone the case for relaxed reciprocity in freeing trade - Bhagwati Jagdish (Cambridge MIT Press, 2002)
This book examines the experiences with an unilateral trade liberalization. Part 1 considers historical experiences, following Britain?s unilateral embrace of free trade. Part 2 discusses recent examples, and Part 3 discusses unilateral liberalization in
Keywords: Commercial policy; Free trade; International economic relations; International trade